2019
DOI: 10.3126/qjmss.v1i2.27445
|View full text |Cite
|
Sign up to set email alerts
|

Communication in Banking Sector: A Systematic Review

Abstract: Background: Effective banking communication strengthens the relationship between customer, suppliers, stakeholders, manager, client, employees and board of directors. Banker’s experience on banking communication enhances banking system, employee’s behavior and core banking services facilities management. Banking communication improves organizational effectiveness through training, knowledge management, risk management, internal control system and data security management. In modern era, communication channel i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Likewise, Laketa et al (2015) indicated the necessity for banks to employ new communication channels such as social networks in creating integration within the communication channels they use, because the use of these networks will contribute to improving customer service and building strong relationships with customers. Shrestha et al (2019); Armstrong et al (2020) argued that effective banking communications with the customer will not be achieved without the use of electronic media, it is a prerequisite for exchanging messages and reaching a common understanding that will ultimately support the relationship between the two parties and improve the customer experience. Therefore, banks should constantly evaluate and reconsider their investments related to customer communications.…”
Section: The Relationship Between E-crm and Customer Experience In E-...mentioning
confidence: 99%
“…Likewise, Laketa et al (2015) indicated the necessity for banks to employ new communication channels such as social networks in creating integration within the communication channels they use, because the use of these networks will contribute to improving customer service and building strong relationships with customers. Shrestha et al (2019); Armstrong et al (2020) argued that effective banking communications with the customer will not be achieved without the use of electronic media, it is a prerequisite for exchanging messages and reaching a common understanding that will ultimately support the relationship between the two parties and improve the customer experience. Therefore, banks should constantly evaluate and reconsider their investments related to customer communications.…”
Section: The Relationship Between E-crm and Customer Experience In E-...mentioning
confidence: 99%
“…However, it is necessary to examine more carefully regarding the role of communication in participative decision making. According to Shrestha et al (2019) effective communication in banks promotes cooperation, increases efficiency, productivity, and job satisfaction. Further, it also increases external and internal communication between employees and managers.…”
Section: Introductionmentioning
confidence: 99%